Penanganan Fisioterapi Kasus Delay Motor Development (DMD) Dengan Intervensi Stimulasi - Dimas Nur Ivandi; Erica Nur Fitria; Indra Fadhilah Hakim; Rumthe Domitila; Dini Nur Alpiah (JOURNAL SAINS STUDENT RESEARCH, 2025)
Early detection and appropriate intervention, such as physiotherapy with stimulation, are crucial to optimizing a child's motor development potential. This study aims to analyze the physiotherapy management of a case of Developmental Motor Delay (DMD) using stimulation interventions. The research employs a descriptive qualitative case study design involving one child aged 10 to 18 months diagnosed with DMD at the Physiotherapy Room of the Tumbuh Kembang Sejahtera Clinic. Data were collected through initial and final assessments. Stimulation interventions were administered twice a week over a four-week period. Data analysis was conducted descriptively by comparing AIMS scores before and after the intervention, as well as by describing the therapeutic process and responses. The results showed that in the initial assessment, the subject experienced significant delays in gross motor development. After four weeks of stimulation intervention, there was a significant improvement in the subject's AIMS score. The subject demonstrated the ability to roll independently, sit without assistance, and began to show attempts at crawling, appearing more active and responsive.